Reversible inactivation of the nucleus basalis magnocellularis induces disruption of cortical acetylcholine release and acquisition, but not retrieval, of aversive memories - Miranda, María Isabel (The National Academy of Sciences, 1999)
The basal forebrain complex, which includes the nucleus basalis magnocellularis (NBM), provides widespread cholinergic and γ-aminobutyric acid-containing projections throughout the brain, including the insular and pyriform cortices. A number of studies have implicated the cholinergic neurons in the mediation of learning and memory processes. However, the role of basal forebrain activity in information retrieval mechanisms is less known. The aim of the present study is to evaluate the effects of reversible inactivation of the NBM by tetrodotoxin (TTX, a voltage-sensitive sodium channel blocker) during the acquisition and retrieval of conditioned taste aversion (CTA) and to measure acetylcholine (ACh) release during TTX inactivation in the insular cortex, by means of the microdialysis technique in free-moving rats. Bilateral infusion of TTX in the NBM was performed 30 min before the presentation of gustative stimuli, in either the CTA acquisition trial or retrieval trial. At the same time, levels of extracellular ACh release were measured in the insular cortex. The behavioral results showed significant impairment in CTA acquisition when the TTX was infused in the NBM, whereas retrieval was not affected when the treatment was given during the test trial. Biochemical results showed that TTX infusion into the NBM produced a marked decrease in cortical ACh release as compared with the controls during consumption of saccharin in the acquisition trial. Depleted ACh levels were found during the test trial in all groups except in the group that received TTX during acquisition. These results suggest a cholinergic-dependent process during acquisition, but not during memory retrieval, and that NBM-mediated cholinergic cortical release may play an important role in early stages of learning, but not during recall of aversive memories.